PENGHAMBATAN PERTUMBUHAN Aspergillus flavus DAN Fusarium moniliforme OLEH EKSTRAK SERUNI (Wedelia biflora) DAN KEMBANG BULAN (Tithonia diversifolia) - Agnes Dame Sinta Uli; Kiki Nurtjahja; Cut Fatimah Zuhra (Saintia Biologi, 2012)
The growth inhibition of Aspergillus flavus and Fusarium moniliforme by extract of seruni (Wedelia biflora) and Kembang bulan (Tithonia diversifolia) has studied. Kirby-Bauer disc diffusion were used in this experiment. The leaf methanolic extracts prepared were 0, 5, 10, 15, 30, 40, 50, 60 and 70% with  dimethyl sulfoxide as the solvent. The results showed that extract of seruni and kembang bulan  has a different activity in inhibiting the growth of both fungus. Seruni  extract  showed lower activity in inhibiting A. flavus and F. moniliforme than kembang bulan. In 40% seruni  inhibits the growth both of the fungus. While kembang bulan showed activity in inhibiting A. flavus and F. moniliforme in 5%.   Kata kunci: A.  flavus, F.  moniliforme, T. diversifolia and  W. biflora exctract